Sarcomatoid variant of Xp11 translocation renal cell carcinoma: A rare case report in an adult female - Rakhi V. Jagdale; Supriya Jain; Jaydeep N. Pol; Makarand V. Khochikar (Indian Journal of Pathology and Microbiology)
Xp11 translocation renal cell carcinoma (XPTRCC) is a very rare kidney neoplasm, which has been predominantly reported in young patients. Sarcomatoid transformation in renal cell carcinomas is known. However, its occurrence in XPTRCC is unreported so far in the literature. We report a unique case of sarcomatoid transformation in a XPTRCC in a 23-year-old female, who presented with a huge right-sided renal mass and had metastatic deposits in lungs. Morphologically, clear cell morphology with papillary architecture along with foci of sarcomatoid transformation and rhabdoid differentiation were noted. Immunohistochemistry showed Pax-8 and TFE-3 expression in all components including the sarcomatous areas, whereas CK and EMA were expressed in conventional clear cell component. We present an extremely rare case of sarcomatous transformation in XPTRCC and discuss the case as determined by histopathology and immunocytochemistry. To our knowledge, this is the first case of sarcomatoid transformation XPTRCC being reported in the world literature.